Antiretroviral Drug Use in a Cross-Sectional Population Survey in Africa: NIMH Project Accept (HPTN 043). (1st February 2017) - Fogel, Jessica M.; Clarke, William; Kulich, Michal; Piwowar-Manning, Estelle; Breaud, Autumn; Olson, Matthew T.; Marzinke, Mark A.; Laeyendecker, Oliver; Fiamma, Agnès; Donnell, Deborah; Mbwambo, Jessie K. K.; Richter, Linda; et al.
Abstract : Background: Antiretroviral (ARV) drug treatment benefits the treated individual and can prevent HIV transmission. We assessed ARV drug use in a community-randomized trial that evaluated the impact of behavioral interventions on HIV incidence. Methods: Samples were collected in a cross-sectional survey after a 3-year intervention period. ARV drug testing was performed using samples from HIV-infected adults at 4 study sites (Zimbabwe; Tanzania; KwaZulu-Natal and Soweto, South Africa; survey period 2009–2011) using an assay that detects 20 ARV drugs (6 nucleoside/nucleotide reverse transcriptase inhibitors, 3 nonnucleoside reverse transcriptase inhibitors, and 9 protease inhibitors; maraviroc; raltegravir). Results: ARV drugs were detected in 2011 (27.4%) of 7347 samples; 88.1% had 1 nonnucleoside reverse transcriptase inhibitors ± 1–2 nucleoside/nucleotide reverse transcriptase inhibitors. ARV drug detection was associated with sex (women>men), pregnancy, older age (>24 years), and study site ( P < 0.0001 for all 4 variables). ARV drugs were also more frequently detected in adults who were widowed ( P = 0.006) or unemployed ( P = 0.02). ARV drug use was more frequent in intervention versus control communities early in the survey ( P = 0.01), with a significant increase in control ( P = 0.004) but not in intervention communities during the survey period. In KwaZulu-Natal, a 1% increase in ARV drug use was associated with a 0.14% absolute decrease in HIV incidence ( P = 0.018). Conclusions: This study used an objective, biomedical approach to assess ARV drug use on a population level. This analysis identified factors associated with ARV drug use and provided information on ARV drug use over time. ARV drug use was associated with lower HIV incidence at 1 study site. Abstract : Supplemental Digital Content is Available in the Text.